Digital Ultrasonography for the Horse - Alison Morton (EDIS)
The veterinarians of the University of Florida Equine Lameness & Imaging Service specialize in the treatment and rehabilitation of poor performance in sport horses. This series of one-page full color fact sheets describes various diagnostic and imaging services available for diagnosing and treating lameness issues in horses.